PENERAPAN PENDEKATAN INTERAKSI EDUKATIF UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS II SDN 007 SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Sahdeli, Sahdeli (Jurnal Manajemen Pendidikan, 2022)
This research was motivated by the low learning outcomes of Indonesian class II students so that the learning outcomes did not meet the KKM, namely 75, for this reason the researchers sought to improve Indonesian learning outcomes by using an educative interaction approach at SD Negeri 007 Simandolak, Benai District, Kuantan Singingi Regency. Class Action Research is carried out to improve student learning outcomes by applying the Educative Interaction Approach to Indonesian language lessons. This research was conducted in class II of SDN 007 Simandolak, Benai District, Kuantan Singingi Regency. This research was conducted in two cycles, each cycle consisting of four research steps, namely planning, implementing, observing and reflecting. To obtain the research data, an observation sheet filled in by the observer and a learning achievement test are used at the end of the cycle. Student learning activity data was analyzed by determining the number and percentage of students involved in each meeting. Improved learning outcomes seen from the number of students who complete at the end of the cycle. The results showed that learning activities and student learning outcomes increased after 2 cycles of improvement. 56.75% of students have very good grades while 43.25% are good, so students who have completed 100%. from this data it can be concluded that the application of the Educative Interaction Learning Model can improve Indonesian learning outcomes.